Tác động của thiên tai đối với tăng trưởng kinh tế Việt Nam: Tiếp cận theo mô hình VAR - Nguyễn Khắc, Hiếu; Nguyễn Hoàng, Bảo (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
This paper aims to investigate the impact of natural disasters on economic growth in Vietnam from 2004 to 2015, and also the impact of natural disasters on other parameters such as foreign direct investment, foreign trade, inflation, and interest rates. The results of VAR model show that natural disasters have negative impacts on economic growth and foreign trade. However, with the existing data we find that natural disasters have no impact on foreign direct investment, inflation, and interest rates. From the results above we also propose some measures to reduce the impact of natural disasters on Vietnam’s economy.
Keywords: Natural disaster; economic development; VAR